PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Pada Perusahaan Food and Beverages Yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Febi Mulyasari; Abdul Qodir Djaelani; Muhammad Agus Salim (UNIVERSITAS ISLAM MALANG, 2017)
Abstract This study aims to determine the effect of corporate governance structure, on the financial performance of the company. The population in this research is food and beverage companies listed in Indonesia Stock Exchange in the year 2013-2015 as many as 20 companies. The sample in this research using purposive sampling technique as many as 18 companies. Data analysis method used in this research is multiple linear regression. The results of this study indicate that there is a significant correlation between managerial, institutional, independent commissioners and audit committees that affect the performance of food and beverage companies listed on the Indonesia Stock Exchange. Partially Test results show that stakeholders are insignificant to company performance (sig 0,469), institutional institutions significant to financial performance (sig 0,010), independent commissioner is not significant to financial performance (0,976) and audit committee significant to financial performance (0,029). Keywords: good corporate governance, managerial ownership, accounting firm, independent commissioner, and audit committee.